THE EFFECT OF ORGANIZATIONAL CLIMATE AND SERVANT LEADERSHIP ON JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE PERFORMANCE (STUDY ON THE REGIONAL LIAISON AGENCY FOR BANTEN PROVINCE IN JAKARTA) - Arijanto, Agus; Widayati, C. Catur; Pramudito, Onggo (Dinasti International Journal of Digital Business Management, 2022)
This study aims to determine the influence of organizational climate and servant leadership on job satisfaction and its impact on employee performance. Design this study with explanatory. The population in this study were employees of the Banten Provincial Litraison Agency in Jakarta. The data collection technique in this study was by disibuting questionnaires directly to the object of the study, namely employees of the Banten Provincial Liaison Agency in Jakarta. The population of this study was employees of the Banten Provincial Liaison Agency in Jakarta with a total of 124 people. Quantitative analysis methods with SEM analysis tools and Smart PLS 3.3 tools. The findings in this study are: (1) The organizational climate has a positive and insignificant effect on job satisfaction; (2) Servant leadership has a positive and significant effect on employee performance; (3) The organizational climate has a positive and unsavory effect on job satisfaction; (4) Servant leadership has a negative and significant effect on employee performance; (5) Job satisfaction has a positive and significant effect on employee performance.